Small Dual-Band 3D Beamforming MIMO Antenna - Zandamela, Abel Abdul; Marchetti, Nicola; Narbudowicz, Adam (IEEE, 2023)
This work proposes a small dual-band (2.4 GHz and 4.89 GHz bands) 3D beamforming Multiple-Input Multiple-Output (MIMO) antenna for emerging size-constrained Internet of Things (IoT) applications. The performance is realized via digital beamforming in a structure sized only 51.5 mm in diameter (smaller than half wavelength at 2.4 GHz). At the 2.4 GHz band, the antenna realizes an isolation > 30 dB, and the Envelope Correlation Coefficient (ECC) is < 0.0003), with a bi-directional beamforming capability in the azimuth plane and unidirectional beamforming across the elevation plane. At the 4.89 GHz band, the isolation is > 19 dB, and the ECC< 0.0047, while unidirectional beamforming is achieved in both the azimuth and elevation planes.
European Microwave Conference
Keywords: Small IoT Devices; MIMO Antennas; Multimode Antennas; Multi-band Antennas; Beamforming Antennas; Telecommunications; Antennas; ELECTRONICS; MIMO Antennas; Multi-band Antennas; SMALL ANTENNAS